Phoenician Bronze and Silver Bowls from Cyprus and the Mediterranean - Markoe, Glenn (1985)
davon 134 Taf., darunter auch vergleichendes Material aus Syrien, Anatolien, Assyrien, Iran; pp. 90-148: Phoenician influence abroad, spez. 102-105 Assyria, 105-110 Iran.